Propensity of Tampons and Barrier Contraceptives to Amplify Staphylococcus aureusToxic Shock Syndrome Toxin-I - Philip M. Tierno; Bruce A. Hanna (Hindawi Limited, 1994)
Objective: Although the incidence of reported cases of toxic shock syndrome (TSS) has declined in recent years, the disease continues to occur in menstruating women using the newer, less-absorbent tampons or barrier contraceptives. Extant tampons and other vaginal devices were tested for the ability to induce TSS toxin-1 (TSST-1) by a TSS strain of Staphylococcus aureus MN8, a known high-toxin producer. Tested for the first time were 20 varieties of tampons, including 2 all-cotton brands newly introduced in the United States, a polyurethane contraceptive sponge, a latex diaphragm, and a polymer menstrual collection cup.